Community planning of social services in the Central Bohemia region - Kubečková, Markéta (Univerzita Pardubice, 2009)
The community planning of social services (CPSS) method focuses at planning the development of social services at a local and regional level. CPSS ensures the effective functioning of social services and allows for the efficient use of funds. The goal is to provide accessible services at a level of higher-quality, which respond to the current needs of users and are transparent, with funding allotted only to those services which are really needed etc..
Keywords: Community Planning; Social Services; Central Bohemia region; community planning methods; law on social services; development plans; planning processes